Alternative Splicing Programs in Prostate Cancer - Claudio Sette (International Journal of Cell Biology)
Prostate cancer (PCa) remains one of the most frequent causes of death for cancer in the male population. Although the initial antiandrogenic therapies are efficacious, PCa often evolves into a hormone-resistant, incurable disease. The genetic and phenotypic heterogeneity of this type of cancer renders its diagnosis and cure particularly challenging. Mounting evidence indicates that alternative splicing, the process that allows production of multiple mRNA variants from each gene, contributes to the heterogeneity of the disease. Key genes for the biology of normal and neoplastic prostate cells, such as those encoding for the androgen receptor and cyclin D1, are alternatively spliced to yield protein isoforms with different or even opposing functions. This review illustrates some examples of genes whose alternative splicing regulation is relevant to PCa biology and discusses the possibility to exploit alternative splicing regulation as a novel tool for prognosis, diagnosis, and therapeutic approaches to PCa.